Analisis Kelayakan Finansial Dan Sensitivitas Usahatani Anggur Di Desa Banjar Kecamatan Banjar Kabupaten Buleleng - MANDALA, NGURAH ADI PUTRA; DARMAWAN, DWI PUTRA; WIDYANTARA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.4, Oktober 2019, 2019)
Financial Feasibility Analysis and Grapes Farming Sensitivity in Banjar Village, Banjar District, Buleleng Regency. Bali Grapes, especially those in Buleleng Regency, are one of the superior products of the region with a large potential to be developed. Bali Grapes have been cultivated for a long time in several sub-districts, one of them in Banjar District. Grape farming is sought to get maximum profit during its economic life. This study aims to: (1) Knows the feasibility of grape farming in the Banjar Village, Banjar District, Buleleng Regency. (2) Knowing the sensitivity level of NPV, IRR, Net B/C, and Payback Period on grapes farming in Banjar Village, Banjar District, Buleleng Regency. Location selection is done purposively. The data used includes primary data and secondary data. Primary data were obtained from questionnaires and interviews. Secondary data was obtained from various literatures and several related agencies. Data retrieval was carried out in July to August 2018. The analysis carried out included farming feasibility: NPV, IRR, Net B/C, PP, and Sensitivity. The results showed that: (1) Grapes farming is feasible to be developed financially, because the NPV value > 0, Net B/C > 1, IRR > applicable interest rates, and capital returns with a time limit of less than 8 years. (2) The sensitivity / sensitivity of grape farming occurs in the decline in the selling price of wine, in the decline in production and in the increase in production costs, so that wine farming becomes inappropriate.